Critical assessment of occupational health hazard in hospitality industry in Kano state, Nigeria - Abdullahi, Yusuf M.; Garba, Hamza; Baba, Ibrahim; Musa, Abuhuraira Ado; Muhammad, Faisal (International Journal of Scientific Reports, 2021)
Background: It is a known fact that different occupations are occupied with different forms of hazard. Regardless to the nature, size and the enterprise scope of operation, the occupations available in the enterprise are no doubt associated with one form of hazard or the other. The purpose of this study was to critically assess the occupational hazard in hospitality industry in Kano state. Methods: A total of 384 people from the selected hotels were recruited to form the sample of the study using simple random sampling technique. The instrument used for data collection in the study was self-administered semi-structured questionnaire. Data collected were analysed using statistical package for the social sciences (SPSS) version 20. Results: In this study 50.0% of the respondents were ≤25 years and 54.9% of the respondents were male. More than three-fifths (64.0%) were civil servants, and most of the respondents (63.0%) were single. About 53.4% of them had tertiary level of education and above. Slightly below four-fifths (79.9%) of the respondents knew about physical work hazard and 75.0% of them were aware that physical work hazard can cause ailment and subsequently ill-health to employees and customers. Close to seven-tenths (69.8%) of the respondents understood what is meant by biological factors when issue relating to work hazard is being addressed. Little above half (53.4%) of the respondents knew what chemical hazard is all about and 75.8% of the respondents mentioned that if workable measures are implemented, this will reduce the occurrence of work related hazards. Conclusions: There is lack of proper knowledge regarding the physical, chemical and biological hazards among the study participants. Government must provide suitable and enforcement laws that will enforce laws towards sustainable organizational safety.